2005
DOI: 10.1161/01.hyp.0000151323.93372.f5
|View full text |Cite
|
Sign up to set email alerts
|

Selective Angiotensin-Converting Enzyme C-Domain Inhibition Is Sufficient to Prevent Angiotensin I–Induced Vasoconstriction

Abstract: Abstract-Somatic angiotensin-converting enzyme (ACE) contains 2 domains (C-domain and N-domain) capable of hydrolyzing angiotensin I (Ang I) and bradykinin. Here we investigated the effect of the selective C-domain and N-domain inhibitors RXPA380 and RXP407 on Ang I-induced vasoconstriction of porcine femoral arteries (PFAs) and bradykinin-induced vasodilation of preconstricted porcine coronary microarteries (PCMAs). Ang I concentrationdependently constricted PFAs. RXPA380, at concentrations Ͼ1 mol/L, shifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
1
45
0
1
Order By: Relevance
“…This is very different from the N-terminal-inactivated mice, ACE7/7, which had a response to Ang I infusion equivalent to wild-type mice. 11 This observation is also in accordance with a previous publication from van Esch et al 26 They also showed a predominant role of the C-terminus in the in vivo conversion of Ang I to Ang II.…”
Section: Discussionsupporting
confidence: 92%
“…This is very different from the N-terminal-inactivated mice, ACE7/7, which had a response to Ang I infusion equivalent to wild-type mice. 11 This observation is also in accordance with a previous publication from van Esch et al 26 They also showed a predominant role of the C-terminus in the in vivo conversion of Ang I to Ang II.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of aldosterone-induced vasodilation in HCAs may relate to our inability to observe endothelial NO release in these vessels. 23 Limited NO release could also underlie the absence of a vasodilator response to 17␤-estradiol in HCAs. Despite the higher incidence of stroke, myocardial infarction, and dementia in postmenopausal women taking hormone replacement therapy, 24 virtually all in vitro studies published so far claim that estrogen induces vasodilation through endothelium-dependent or endothelium-independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin I, although it is an ACE substrate, does not elicit the phosphorylation of ACE on Ser1270 (Kohlstedt et al, 2004) and was also unable to elicit the phosphorylation of MYH9. Because selective inhibition of the C-domain active center of ACE is sufficient to inhibit the conversion of angiotensin I, whereas bradykinin is a substrate for both the N-and C-terminal active centers (van Esch et al, 2005), it is tempting to suggest that angiotensin I does not interact with the appropriate site on ACE to elicit ACE signaling.…”
Section: Myh9 Phosphorylation By Ace Signaling 23mentioning
confidence: 99%